Pemberdayaan masyarakat melalui inovasi pembuatan permen Madu Trigona dan Nira desa Sigar Penjalin - Pertiwi, Made Gendis Putri; Sinaga, Yesica Marcelina Romauli; Rasyda, Riezka Zuhriatika; Pawestri, Setyaning; Perdana, Firman Fajar; Utama, Qabul Dinanta; Unsunnidhal, Lalu; Anggraini, Ines Marisya Dwi; Handito, Dody; Fuadi, Mi’raj; Saputra, Oki; Antesty, Sella; Amaliah, Wenny; Wardatullatifah S., Ince Siti; Yasa, I Wayan Sweca (ABSYARA: Jurnal Pengabdian Pada Masayarakat, 2023)
Stunting remains an unresolved issue in North Lombok, NTB, Indonesia. One of the government's efforts to reduce stunting rates involves ensuring nutritional fulfillment for mothers and expectant mothers, which can be obtained from local food sources. Nira (palm sap) and Trigona honey are local commodities available in Tanjung, North Lombok. Unfortunately, these commodities have not been optimally utilized for nutritional fulfillment or as income sources. Typically, Nira is only sold as fresh sap, fermented beverage (tuak), or palm sugar, which have relatively low market values. Combining Nira and Trigona honey to create high-value candy products represents an opportunity. This community service project aimed to improve welfare and nutrition in Sigar Penjalin Village by assisting in the production of hard candy from Trigona honey and Nira Aren as a potential local delicacy to combat stunting and enhance local income. The implementation involved 16 community members organized by UMKM Rangsot Kreatif. The training used ingredients like brown sugar, granulated sugar, glucose syrup, Trigona honey, and water. The training stages included preparation, material delivery, hands-on practice, and evaluation through pretests and posttests to measure participants' knowledge, skills, and interests. The pretest results showed a total score of 627 out of 960 (65.31%), indicating a moderate level of understanding. After the training, the posttest showed a significant improvement, with a total score of 829 out of 960 (86.35%), indicating a very high level of understanding. This activity highlights the importance of technological support and the utilization of local resources in developing nutritious and economical snack products, supporting improvements in community nutrition and economy, and providing alternative solutions in local product processing